2018
DOI: 10.1186/s12967-018-1714-1
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted imaging and diffusion kurtosis imaging for early evaluation of the response to docetaxel in rat epithelial ovarian cancer

Abstract: BackgroundTo investigate diffusion-weighted magnetic imaging (DWI) and diffusion kurtosis magnetic imaging (DKI) for the early detection of the response to docetaxel (DTX) chemotherapy in rat epithelial ovarian cancer (EOC).Methods7,12-Dimethylbenz[A]anthracene was applied to induce orthotopic EOC in Sprague–Dawley rats. Rats with EOC were treated with DTX on day 0 (treatment group) or were left untreated (control group). DWI and DKI were performed on days 0, 3, 7, 14 and 21 after treatment. On day 21, the tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Several studies have shown that diffusion MRI is a sensitive and early indicator of both treatment response and overall survival in brain tumors, [43][44][45] kurtosis parameters showed early and larger changes in detecting response to docetaxel chemotherapy in rat epithelial ovarian cancer. 47 The current study showed the axial kurtosis metric to be more sensitive to studying early RT related changes in the tumor offering a 13.3% larger effect sizes than corresponding diffusion metrics in the active tumor regions. This increased sensitivity is also seen in the evaluation of microstructural changes in low-grade gliomas as compared to DTI imaging, where DKI offers significant increases in the effect sizes for delineating different regions of the gross tumor.…”
Section: Discussionmentioning
confidence: 60%
“…Several studies have shown that diffusion MRI is a sensitive and early indicator of both treatment response and overall survival in brain tumors, [43][44][45] kurtosis parameters showed early and larger changes in detecting response to docetaxel chemotherapy in rat epithelial ovarian cancer. 47 The current study showed the axial kurtosis metric to be more sensitive to studying early RT related changes in the tumor offering a 13.3% larger effect sizes than corresponding diffusion metrics in the active tumor regions. This increased sensitivity is also seen in the evaluation of microstructural changes in low-grade gliomas as compared to DTI imaging, where DKI offers significant increases in the effect sizes for delineating different regions of the gross tumor.…”
Section: Discussionmentioning
confidence: 60%
“…20 In orthotopic preclinical models of solid ovarian tumours, the change in ADC following docetaxel also was shown to correlate negatively with Ki67, CA125 and Bcl-2, all of which predict residual tumour burden. 21 Although negative correlation between cell density and diffusivity is widely accepted, 22,23 the literature is inconclusive about the effect of stroma, fibrosis and inflammatory infiltrate on ADC values indicating that they are influenced by a complex interplay of biophysical processes. 24,25 In a tissue comprised primarily of fat, such as the omentum, the return of normal fatty stroma interspersed with residual tumour may obscure a posttreatment ADC rise.…”
Section: Discussionmentioning
confidence: 99%
“… 20 In orthotopic preclinical models of solid ovarian tumours, the change in ADC following docetaxel also was shown to correlate negatively with Ki67, CA125 and Bcl-2, all of which predict residual tumour burden. 21 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MD value increased significantly during treatment. This could be attributed to postradiotherapeutic changes, such as tumor lysis, loss of cell membrane integrity, and increased extracellular space, which promotes the movement of water molecules, thereby increasing the diffusion of water (14). Liu et al (15) reported that the MD of osteosarcoma The MK of the good response group was significantly lower than the pre-treatment value, and there was no significant difference in MK between good response and poor response groups.…”
Section: Discussionmentioning
confidence: 99%